P031 Impact of nutritional antigens in inflammatory bowel disease patients. (25th January 2019) - Rodríguez Sillke, Y; Schumann, M; Lissner, D; Branchi, F; Glauben, R; Siegmund, B
Abstract: Background: Inflammatory bowel disease (IBD) represents a dysregulation of the mucosal immune system. The combination of genetic predisposition and environmental factors, as microbiota and food antigens, seems to result in disease development. The pathogenesis of Crohn′s disease (CD) and Ulcerative colitis (UC) but also coeliac disease is linked to the loss of intestinal tolerance and barrier function. The healthy mucosal immune system has previously been shown to be inert against food antigens. The present study served to analyse food-antigen specific T cells in the peripheral blood of CD and UC patients. Methods: Peripheral blood mononuclear cells of CD and UC patients, either active or in remission, were stimulated with different food antigens. Gluten, ovalbumin and soybean served as food antigens. Healthy controls and coeliac disease patients were included as controls. Gluten-activated CD4 + T cells in the peripheral blood of CD and UC were analysed by a magnetic enrichment of CD154 + cells and a novel subsequent cytometric antigen-reactive T-cell analysis ('ARTE' technology) followed by characterisation of the effector response. Results: Among all tested food antigens, the highest frequency of antigen-specific T cells (CD4 + CD154 + ) was found for gluten. Ovalbumin-specific T cells were nearly not detectable in the peripheral blood, while the reaction to soybean was slightly higher. The highest frequency of gluten antigen-specific T cells was revealed in the peripheral blood of active CD when compared with UC, coeliac disease on a gluten-free diet and healthy controls. Interestingly, CD in remission showed still higher frequencies of gluten-specific T cells than healthy controls. These gluten-specific T cells were characterised by up-regulation of the pro-inflammatory cytokines IFN-γ IL-17A and TNF-α . IFN-γ was exclusively elevated in CD patients with active disease. Gluten-specific T cells expressing IL-17A were increased in all IBD patients, again with the highest frequency in active CD patients. Furthermore, T cells of CD patients independent of disease activity revealed a high expression of the pro-inflammatory cytokine TNF- α. Conclusions: We are able to analyse and quantify food antigen specific T cells in the peripheral blood of IBD patients. The detected differences in the effector response of these cells leads to a diagnostic characterisation within the patients groups in IBD. Furthermore, we identified gluten as immune stimulatory antigen also in CD patients. Additionally, these results demonstrate the modulation of the immune compartment, even in the periphery, by intestinal barrier disruption.